PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA TERNATE - Nurlaela Nurlaela; Ruslan A Kamis (Jurnal Manajemen Sinergi, 2020)
This study aims to determine the effect of transformational leadership style and work discipline on employee performance in the Office of Industry and Trade of Ternate City. In this study, the independent variables of transformational leadership style have five indicators and work discipline has four indicators, while the dependent variable, employee performance has five indicators. The population in this study included all employees of the Office of Industry and Trade of Ternate City, amounting to 121 people and obtained a sample of 93 respondents. The analytical method used in this study is multiple linear regression analysis with the help of the SPSS application. Based on the results of the hypothesis test conducted, it was found that transformational leadership style and work discipline significantly influence employee performance both partially and simultaneously